Efficacy of Systolic Extinction Training in Fibromyalgia Patients With Elevated Blood Pressure Response to Stress: A Tailored Randomized Controlled Trial. Issue 5 (25th April 2019) - Thieme, Kati; Meller, Tina; Evermann, Ulrika; Malinowski, Robert; Mathys, Marc G.; Graceley, Richard H.; Maixner, William; Turk, Dennis C.
Abstract : Objective: An intrinsic pain regulatory system is modulated by both cardiovascular dynamics that influence baroreflex sensitivity (BRS) and is diminished in fibromyalgia (FM). Baroreceptors relay cardiovascular output to the dorsal medial nucleus tractus solitarius reflex arcs that regulate pain, sleep, anxiety, and blood pressure. The aim of this study was to evaluate the effects of systolic extinction training (SET), which combines operant treatment (OT) with baroreflex training (BRT). BRT delivers peripheral electrical stimulation within a few milliseconds of the systolic or diastolic peak in the cardiac cycle. In addition, we compared SET to OT–transcutaneous electrical stimulation (TENS) independent of the cardiac cycle and aerobic exercise (AE)–BRT in FM patients with elevated blood pressure responses to stress. Methods: Sixty‐two female patients with FM were randomized to receive either SET (n = 21), OT‐TENS (n = 20), or AE‐BRT (n = 21). Outcome assessments were performed before treatment (T1), after 5 weeks of treatment (T2), and after the 12‐month follow‐up (T3). Results: In contrast to patients receiving OT‐TENS or AE‐BRT, those receiving SET reported a significantly greater reduction in pain and pain interference (all P < 0.01) that was maintained at the 12‐month follow‐up. Clinically meaningful pain reduction at T3 was achieved in 82% of patients in the SET group, 39% of those in the OT‐TENS group, and only 14% of those in the AE‐BRT group. Patients in the SET group showed a significant increase (57%) in BRS following treatment, while neither the AE‐BRT group or the OT‐TENS group showed significant changes over time. Conclusion: SET resulted in statistically significant, clinically meaningful, and long‐lasting pain remission and interference compared to OT‐TENS and AE‐BRT. These results suggest that BRS modification is the primary mechanism of improvement. Replication of our results using larger samples and extension to other chronic pain conditions appear to be warranted.